Visible light-driven photodynamic therapy for hypertrophic scars with MOF armored microneedles patch - Chen, Danyang; Zhang, Yixuan; Long, Wei; Chai, Langjie; Myint, Thazin Phoone; Zhou, Wei; Zhou, Ling; Wang, Min; Guo, Liang (Frontiers in Chemistry, 2023)
Photodynamic therapy (PDT) is widely used for the treatment of hypertrophic scars in clinical practice. However, the low transdermal delivery of photosensitizers in scar tissue and protective autophagy induced by Photodynamic therapy greatly reduces the therapeutic efficiency. Therefore, it is necessary to deal with these difficulties for overcoming obstacles in Photodynamic therapy treatment. In this study, a photosensitizer with photocatalytic performance was designed and synthesized using innovative MOFs (metal-organic frameworks). Additionally, the MOFs, together with an autophagy inhibitor chloroquine (CQ), was loaded in a high mechanical strength microneedle patch (MNP) for transdermal delivery. With these functionalized MNP, photosensitizers and chloroquine were delivered deep inside hypertrophic scars. Inhibition of autophagy increases the levels of reactive oxygen species (ROS) under high-intensity visible-light irradiation. Multiprong approaches have been used to remove obstacles in Photodynamic therapy and successfully enhance its anti-scarring effect. In vitro experiments indicated that the combined treatment increased the toxicity of hypertrophic scar fibroblasts (HSFs), downregulated the level of collagen type I expression as well as transforming growth factor-β1 (TGF-β1)expression, decreased the autophagy marker protein LC3II/I ratio, increased the expression of P62. In vivo experiments showed that the MNP had good puncture performance, and significant therapeutic effects were observed in the rabbit ear scar model. These results indicate that functionalized MNP has high potential clinical value.